2016
DOI: 10.22192/ijcrms.2016.02.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music therapy, aerobic exercise and combined intervention on psychological and physiological parameters in collegiate athletes: A comparative study

Abstract: Aim of the study is to compare the effect of three forms of interventions: relaxing music, aerobic exercise, and both in combination, on state and trait anxiety, RPE and HR in collegiate athletes. Subject: Thirty five collegiate athletes were recruited with inclusion and exclusion criteria and randomly allocated into one of the three groups. Methodology: Each group were performed with different interventions, Group 1-music therapy, group 2-aerobic exercise, group 3-music with aerobic exercise. The intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
1
6
1
1
Order By: Relevance
“…Figueroa et al (20) also found a reduction in exercise HR after 16 weeks of endurance training in obese individuals. These results support our previous finding that aerobic exercise along with relaxing music reduces HR to a greater extent than aerobic exercise in athletes (36). The mechanism behind this could be the psychobiologi-Asian J Sports Med.…”
Section: Hr and Rpesupporting
confidence: 91%
See 4 more Smart Citations
“…Figueroa et al (20) also found a reduction in exercise HR after 16 weeks of endurance training in obese individuals. These results support our previous finding that aerobic exercise along with relaxing music reduces HR to a greater extent than aerobic exercise in athletes (36). The mechanism behind this could be the psychobiologi-Asian J Sports Med.…”
Section: Hr and Rpesupporting
confidence: 91%
“…cal impact that music has on exercise due to relaxation, reduced muscle tension, and increased blood flow, hence reduced heart rate when compared to the only aerobic group (36). Our study found overweight and obese individuals could be able to continue aerobic exercise for a longer time duration due to music intervention helping the distraction of mental stress during exercise bouts, which might help to achieve greater health benefits.…”
Section: Hr and Rpementioning
confidence: 65%
See 3 more Smart Citations